2009
DOI: 10.1007/s10531-009-9692-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of topsoil removal in restored heathland on soil fauna, topsoil microstructure, and cellulose decomposition: implications for ecosystem restoration

Abstract: Communities of soil macrofauna, oribatid mites, and nematodes as well as vegetation and soil chemistry were studied on twelve plots representing three replicates of the following treatments: agricultural meadow, heathland, and heathland restored either by partial or complete topsoil removal 15 years earlier. We also studied the effect of soil macrofauna on decomposition and the microstructure of the soil surface layer with litterbags in combination with the analysis of thin soil sections. The communities of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…Differences in the community compositions between our treatments may be found at lower taxonomic levels. Frouz et al (2009) also showed that the depth of topsoil removal plays a crucial role in preserving local source populations of soil fauna: a removal of the upper 10-15 cm compared to 40-50 cm allowed survival of a local source population in deeper soil layers, which then can recolonize the newly created habitats.…”
Section: Soil Nematode Communities Recover Fast After Perturbationmentioning
confidence: 98%
See 1 more Smart Citation
“…Differences in the community compositions between our treatments may be found at lower taxonomic levels. Frouz et al (2009) also showed that the depth of topsoil removal plays a crucial role in preserving local source populations of soil fauna: a removal of the upper 10-15 cm compared to 40-50 cm allowed survival of a local source population in deeper soil layers, which then can recolonize the newly created habitats.…”
Section: Soil Nematode Communities Recover Fast After Perturbationmentioning
confidence: 98%
“…A combination of removing the topsoil-typically between 20 and 50 cm (e.g. Frouz et al, 2009)-and introducing propagules of target plant species proofed, in contrast, successful (e.g. Kiehl & Pfadenhauer, 2007) and became a promising tool for nature conservation agencies and practitioners in various European countries (Kiehl, Kirmer, Donath, Rasran, & Hölzel, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although reclamation strategies such as the planting of specific tree species or leaving the heap unreclaimed greatly affect soil formation on post‐mining sites (Frouz et al, ; ; ), their effects on soil hydrological properties and water balance are insufficiently understood (Mazur, Schoenheinz, Biemelt, Schaaf, & Grünewald, ). The soil water regime of these heterogeneous dumps is generally influenced by soil properties, climatic, and management factors.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the exploitation margin plot is only at close proximity to the quarrying area, where the intense effects of soil and vegetation removal have not yet been felt, the disturbance effects are already looming over this area. Sources for this disturbance involve the removal and movement of topsoil (Frouz et al ) and vibrations produced by heavy machinery during raw material extraction (Polajnar et al ).…”
Section: Discussionmentioning
confidence: 99%